![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(4,5+\frac{3}{4}x\right):\frac{8}{3}=\frac{9}{8}\)
\(4,5+\frac{3}{4}x=\frac{9}{8}\times\frac{8}{3}\)
\(4,5+\frac{3}{4}x=3\)
\(\frac{3}{4}x=3-4,5\)
\(\frac{3}{4}x=-1.5\)
\(x=-1,5:\frac{3}{4}\)
\(x=\frac{-3}{2}:\frac{3}{4}\)
\(x=\frac{-3}{2}\times\frac{4}{3}\)
\(x=-2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) |x + 2| = 4
\(\Leftrightarrow\orbr{\begin{cases}x+2=4\\x+2=-4\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=2\\x=-6\end{cases}}\)
2) 3 – |2x + 1| = (-5)
\(\Leftrightarrow\left|2x+1\right|=8\Leftrightarrow\orbr{\begin{cases}2x+1=8\\2x+1=-8\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{7}{2}\\x=\frac{-9}{2}\end{cases}}\)
3) 12 + |3 – x| = 9
\(\Leftrightarrow\left|3-x\right|=-3\)(vô lí)
=>\(x=\varnothing\)
1) I x+2 I=4
\(\Rightarrow\orbr{\begin{cases}x+2=4\\x+2=-4\end{cases}\Leftrightarrow\orbr{\begin{cases}x=2\\x=-6\end{cases}}}\)
2) \(3-|2x+1|=-5\)
\(\Leftrightarrow|2x+1|=8\)
\(\Leftrightarrow\orbr{\begin{cases}2x+1=8\\2x+1=-8\end{cases}\Leftrightarrow\orbr{\begin{cases}2x=7\\2x=-9\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=\frac{7}{2}\\x=\frac{-9}{2}\end{cases}}}\)
3) \(12+|3-x|=9\)
\(\Leftrightarrow|3-x|=-3\)(vô lí vì I 3-x I \(\ge\)0)
![](https://rs.olm.vn/images/avt/0.png?1311)
1)=>3(x-5)(2x+9)+3(x-5)=0=>(x-5)(6x+30)
=>x-5=0=>x=5
6x+30=0=>x=-5
2)=>x^2-16=0=>x=+-4
12-4x=0=>x=3
3)=>9-x^2=0=>x=+-3
4x-8=0=>x=2
4)=>8-x^3=0=>x=3
5^x-125=0=>x=2
5)=>2^x.2^x=8=>2^2x=8=>2x=3=>x=1,5
![](https://rs.olm.vn/images/avt/0.png?1311)
a, x : (-2) = 9
x = 9 . (-2)
x = -18
b, 4x + (-8) = 24
4x = 24 - (-8)
4x = 32
x = 32 : 4
x = 8
c, (3 - x) . (x + 7) = 0
TH1: 3 - x = 0
x = 3
TH2: x + 7 = 0
x = -7
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{1}{4}x-1\right)+\left(\frac{5}{6}x-2\right)-\left(\frac{3}{8}x+1\right)=4,5\)
\(\frac{1}{4}x-1+\frac{5}{6}x-2-\frac{3}{8}x-1=\frac{9}{2}\)
\(\left(\frac{1}{4}x+\frac{5}{6}x-\frac{3}{8}x\right)=\frac{9}{2}+1+2+1\)
\(\frac{17}{24}x=\frac{17}{2}\)
\(x=\frac{17}{2}:\frac{17}{24}\)
\(x=\frac{17}{2}.\frac{24}{17}\)
\(x=\frac{24}{2}\)
\(x=12\)
vậy \(x=12\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. ( 3x - 7 ) 5 = 32
=> 3x - 7 = 32 : 5
=> 3x - 7 = 32/5
=> 3x = 32/5 + 7
=> 3x = 67/5
=> x = 67/5 : 3
=> x = 67/5 . 1/3
=> x = 67/15
Tương tự tiếp. Chúc bạn học tốt!!!
a) ( 3x - 7 ) . 5 = 32
( 3x - 7 ) = 32 : 5
( 3x - 7 ) = 6,4
3x = 6,4 + 7
3x = 13.4
x = 13,4 : 3
x = 4,4666 ..
\(\left(4,5+\frac{3}{4}x\right):\frac{8}{3}=\frac{9}{8}\)
\(\Rightarrow\left(4,5+\frac{3}{4}x\right)=\frac{9}{8}\cdot\frac{8}{3}\)
\(\Rightarrow\left(4,5+\frac{3}{4}x\right)=3\)
\(\Rightarrow4,5+\frac{3}{4}x=3\)
\(\Rightarrow\frac{3}{4}x=3-4,5\)
\(\Rightarrow\frac{3}{4}x=-\frac{3}{2}\)
\(\Rightarrow x=-\frac{3}{2}:\frac{3}{4}\)
\(\Rightarrow x=-2\)
(4,5 + 3/4x ) : 8/3 = 9/8
(45/10 + 3/4x ) : 8/3 =9/8
(9/2 +3/4x ) : 8/3 = 9/8
9/2 + 3/4x=9/8 . 8/3
9/2+3/4x =3
3/4x = 3 - 9/2
3/4x = -3/2
x=-3/2 :3/4
x=-2